Bhabha and his magnificent obsessions - Venkataraman, G. (Hyderabad, Universities Press (India)Limited, 1994)
This book is about the remarkable scientist Homi Jehangir Bhabha who, at the age of eighteen, went to Cambridge to study Physics and started his research career there. In 1939, when Bhabha came to India on a short vacation, he was forced to stay on as the Second World War broke out. This was, of course, a blessing for the country as he later steered the country$1 (Bs scientific destiny. The book records Bhabha$1 (Bs contributions which were in many dimensions and were not just purely scientific.s
Index 207-209p.
Keywords: Physics